Linking integrative plant physiology with agronomy to sustain future plant production - Langensiepen, Matthias; Jansen, Marcel; Wingler, Astrid; Demmig-Adams, Barbara; Adams, William W.I.I.; Dodd, Ian C.; Fotopoulos, Vasileios; Snowdon, Rod John; Fenollosa, Erola; De Tullio, Mario C.; Buck-Sorlin, Gerhard H.; Munné-Bosch, Sergi (My University, 2020)
Sustainable production of high-quality food is one of today’s major challenges of agriculture. To achieve this goal, a better understanding of plant physiological processes and a more integrated approach with respect to current agronomical practices are needed. In this review, various examples of cooperation between integrative plant physiology and agronomy are discussed, and this demonstrates the complexity of these interrelations. The examples are meant to stimulate discussions on how both research areas can deliver solutions to avoid looming food crises due to population growth and climate change. In the last decades, unprecedented progress has been made in the understanding of how plants grow and develop in a variety of environments and in response to biotic stresses, but appropriate management and interpretation of the resulting complex datasets remains challenging. After providing an historical overview of integrative plant physiology, we discuss possible avenues of integration, involving advances in integrative plant physiology, to sustain plant production in the current post-omics era. Finally, recommendations are provided on how to practice the transdisciplinary mindset required, emphasising a broader approach to sustainable production of high-quality food in the future, whereby all those who are involved are made partners in knowledge generation processes through transdisciplinary cooperation.
Keywords: Food production; Molecular plant biology; Plant physiology; Agronomy; Sustainability; Transdisciplinarity